The theology and praxis of practical theology in the context of the Faculty of Theology - Steyn, Tobias H. (HTS teologiese studies, 2011)
Notwithstanding the carefully defined parameters of the various departments within theology, the aspirant student sometimes finds it difficult to define the precise department within which a specific study would best be located. We have discovered that these various fields and departments have many areas of commonality and the borders between them are tested often, even in our own studies. However, we have learned that crossing between one field and another should not be seen as a problem but as strength, as it will enable the researcher to motivate and test his or her theological convictions. It is in this context that the subject of this article finds its motivation. Through it we have argued for a practical theology that will be responsible for engaging with its own theology, in order to find the necessary energy to sustain itself. Not only should practical theology be energised by its theology, it should also, as its name implies, be practical in its nature, offering help to all people in need of pastoral care.